Cartesian impedance control of redundant and flexible-joint robots - Ott, Christian. (Springer Tracts in Advanced Robotics, 2008)
This monograph is devoted to the classical topic of impedance control, which has recently seen renewed interest following advances in the mechanical design of lightweight robotic systems with improved actuation and sensing capabilities. After a general introduction into the topics of impedance control, the book focuses on two key issues, namely the treatment of joint flexibility and kinematic redundancy. Several control laws are developed based on mature approaches such as the singular perturbation theory, cascaded control theory, and passivity. The controllers are compared based on their conceptual potential as well as practical implementation issues. The evaluation was performed through several experiments with the DLR arms and the humanoid manipulator 'Justin'.